RE-POSITIONING THE CONCEPTUAL UNDERSTANDING OF ADULT EDUCATION IN NIGERIA - Ezema, James O (Journal of Continuing and Development Education, 2022)
Re-positioning the conceptual understanding of adult education in Nigeria becomes necessarily important due to the misunderstanding of the meaning or conceptual definition of adult education as a distinct theoretical and practical discipline. As an educational science, the scope of adult education should be well understood and the methodological approach of delivery of such scopes should be made very clear for practitioners. In this paper, the meaning of adult education, the historical development in Nigeria, various definitions of adult education, forms of adult education and types of adult education have been x-rayed. Some challenges facing the theory and practice of adult education in Nigeria were portrayed, conclusion drawn and recommendations made